Effectiveness of Mass Casualty Protocols in Hospitals - Almonte, Natalie; Margery, Nyaluma; Colbian, Kathryn; McNair, Ashli (My University, 2020)
In recent years, mass casualty incidents (MCI’s) have become more prevalent across the United States. We are researching how hospitals are equipped to handle MCI’s. We investigated the question, for hospital staff, what is the effect of training protocols on hospital preparedness for mass causality incidents? We have found that many protocols in place are based upon a simulated event. We wanted to know if hospital staff are adequately prepared based off of simulated training. We conducted a systematic literature review to research the effectiveness of this practice. The key impact of this research is we can discover if these protocols are sufficient or if a need for improvement should be established. We developed a practice protocol to address mass casualty preparedness in hospitals.